Regulatory T Cells Control the Switch From in situ to Invasive Breast Cancer - Martinez, Leandro M.; Robila, Valentina; Clark, Nicholas M.; Du, Wei; Idowu, Michael O.; Rutkowski, Melanie R.; Bos, Paula D. (Frontiers in Immunology, 2019)
Ductal carcinoma in situ is a non-obligate precursor of breast cancer, and it only progresses to invasive breast cancer in around 40% of patients. While immune infiltrates have been observed in these early cancer lesions, their potential prognostic value is still unclear. Regulatory T (Treg) cells accumulate in advanced breast cancers, and predict poor outcome. We have shown before that ablation of Treg cells in established tumors leads to significant decrease in primary and metastatic tumor burden. In this work, we sought to investigate Treg cell function in the progression from non-invasive to invasive breast cancer lesions. To this end, we used the murine mammary tumor virus polyoma middle T (MMTV-PyMT) murine model of spontaneous, stage-wise breast carcinogenesis crossed to Foxp3DTR knockin mice, allowing Treg cell ablation by administration of diphtheria toxin. Transient targeting of Treg cells at the in situ carcinoma stage resulted in a significant increase in the number of tumor-bearing mammary glands and size of growing tumors compared with control mice. Whole mammary gland mounts and histological examination confirmed larger emergent tumor area in Treg cell-ablated mice, and revealed that these tumors were characterized by a more advanced tumor staging, with presence of early invasion, increased desmoplasia and collagen deposition. Furthermore, Treg cell ablation increased the percentage of cancer stem/progenitor cells in the mammary compartment. Interestingly, Treg cell ablation resulted in increased inflammatory cytokines IL-4 and IL-5 with a concomitant reduction in classically activated tumor associated macrophages. This TH2-biased immune regulatory mammary inflammation was consistent with the enhancement in tumor promotion that we observed. Overall, our study demonstrates that Treg cells oppose breast cancer progression at early stages, raising a cautionary note regarding the consideration of immune intervention targeted at boosting immune responses for DCIS.